ACVIZ: A tool for the visual analysis of the configuration of algorithms with irace - Marcelo de Souza; Marcus Ritt; Manuel López-Ibá\~nez; Leslie Pérez Cáceres (Operations Research Perspectives, 2021)
This paper introduces acviz, a tool that helps to analyze the automatic configuration of algorithms with irace. It provides a visual representation of the configuration process, allowing users to extract useful information, e.g. how the configurations evolve over time. When test data is available, acviz also shows the performance of each configuration on the test instances. Using this visualization, users can analyze and compare the quality of the resulting configurations and observe the performance differences on training and test instances.
Keywords: 330; Algorithm configuration; Parameter tuning; irace